2019
DOI: 10.3390/min9080491
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Amphiboles in the Tremolite–Ferro–Actinolite Series by Raman Spectroscopy

Abstract: Amphiboles are an important family of rock forming minerals, whose identification is crucial in provenance studies as well as in many other fields of geology, archaeology and environmental sciences. This study is aimed to find a quick way to characterize Ca-amphiboles in the tremolite (Ca2Mg5Si8O22(OH)2)–ferro–actinolite (Ca2Fe5Si8O22(OH)2) series. Raman spectroscopy is established as technique to perform non-destructive and quick analysis, with micrometric resolution, able to give the composition in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…The tremolite in our study demonstrates no Stokes lines between 3600 and 3700 cm −1 indicating the stretching vibrations of M–OH (M = metal cation). We propose that the intensity of the highest‐wavenumber Raman signal at around 3675 cm −1 has an orientation dependence already implied by Blaha and Rosasco, apart from the composition related effect reported by Bersani et al In addition, tremolite exhibits a Stokes line at 1326 cm −1 , which starts at around 100 K. This Stokes line could be the by‐product of the Raman laser energy interacting with the crystal surface. The Stokes line is consistent with the formation of hematite, as 1326 cm −1 is the strongest Raman feature of this mineral.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The tremolite in our study demonstrates no Stokes lines between 3600 and 3700 cm −1 indicating the stretching vibrations of M–OH (M = metal cation). We propose that the intensity of the highest‐wavenumber Raman signal at around 3675 cm −1 has an orientation dependence already implied by Blaha and Rosasco, apart from the composition related effect reported by Bersani et al In addition, tremolite exhibits a Stokes line at 1326 cm −1 , which starts at around 100 K. This Stokes line could be the by‐product of the Raman laser energy interacting with the crystal surface. The Stokes line is consistent with the formation of hematite, as 1326 cm −1 is the strongest Raman feature of this mineral.…”
Section: Discussionsupporting
confidence: 64%
“…However, it should be added that the spectra were noisy and had a low signal to noise ratio. Talc: The two Stokes lines from the OH group stretching modes of talc occur at 3660 and 3676 cm −1 in RT (Figure b). When cooling down the temperature in vacuum, these Raman shifts show Stokes lines at 3662 and 3677 cm −1 below 250 K. Nevertheless, these shifts are within the spectral resolution and not marked in the figure. Tremolite: Various studies indicate an OH − stretching line for tremolite at around 3675 cm −1 , which we were unable to verify in our work. Nonetheless, EPMA analyses (Table S2) and the characteristic Raman line at 675 cm −1 , related to Si‐O symmetrical stretching (Figure ), confirm that this is a tremolite.…”
Section: Raman Spectroscopy and Resultscontrasting
confidence: 53%
“…[26] On the other hand, it has been shown that for T Al-free amphiboles along the tremolite-ferro-actinolite join, the wavenumber of the ring-breathing mode shifts toward lower wavenumbers with increasing the C Fe 2+ content. [28] Besides, it has been demonstrated that the temperature-induced oxidation of M1 Fe 2+ to M1 Fe 3+ leads to a shift of the ring-breathing mode toward higher wavenumbers. [27] In order to analyze the compositional dependence of the major Raman scattering generated by the TO 4 -ringbreathing mode in more detail, we plotted the position and FWHM of the most intense component of the Raman scattering near 670 cm −1 versus the content of T Al for all the studied samples, representing all major amphibole subgroups (Figure 4a).…”
Section: Quantification Of the Amount Of T Almentioning
confidence: 99%
“…There are several publications, in which the Raman scattering below 1,200 cm −1 has been used to fingerprint amphibole species, and attempts have been made to establish a correlation between the framework spectral features and chemical composition of amphiboles. [23][24][25][26][27][28][29][30] However, most of the studies reported so far are either concerned with a restricted set of samples [24][25][26]28] or focused only on the compositional dependence of the strong Raman peak near 670 cm −1 , [26,28] which originates from the TO 4 -ring-breathing mode. [27] Moreover, the compositional variation of the position of the peak near 670 cm −1 has been ambiguously attributed to different chemical substitutions.…”
mentioning
confidence: 99%
See 1 more Smart Citation